2016
DOI: 10.1002/adv.21778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strain Rate on Tensile Testing of Geogrid Reinforcements Using Single‐Rib and Wide‐Rib Specimen

Abstract: A geogrid is geosynthetic high-density polyethylene material used to reinforce soils and similar materials. It is valuable tool in transportation and civil construction. Geogrids allow engineers to build where it otherwise would not be possible or would be cost prohibitive using traditional methods. The tensile test of the geogrid is the most important test of this product. ISO 10319 "Geosynthetics-Wide-Width tensile test" uses wide-width specimen 20 mm wide; the gripping of this wide sample is difficult and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The strain rate effect on the tensile behavior of geogrids was also studied [ 57 ], in which tests have been conducted according to ISO 10319 standard [ 58 ] considering both single rib and wide-rib specimens at six different strain rates. The study’s objective was to develop a valid method for single rib testing that can be closely matched with the wide-rib test without the need to conduct the wide-width test.…”
Section: Physical and Geometric Characteristicsmentioning
confidence: 99%
“…The strain rate effect on the tensile behavior of geogrids was also studied [ 57 ], in which tests have been conducted according to ISO 10319 standard [ 58 ] considering both single rib and wide-rib specimens at six different strain rates. The study’s objective was to develop a valid method for single rib testing that can be closely matched with the wide-rib test without the need to conduct the wide-width test.…”
Section: Physical and Geometric Characteristicsmentioning
confidence: 99%
“…Balakrishnan and Viswanadham 21 found that the tensile load-strain behaviour of geogrids improved, and their tensile stiffness increased by a maximum of 2.42 times after tensile tests on geogrids inside the soil. Hegazy et al 22 analyzed the difference in tensile properties of single-rib and multi-rib geogrids at different tensile rates through geogrid tensile tests. Chantachot et al 23 evaluated the effect of ambient temperature on the load-strain-time behavior of geogrids using tensile tests.…”
Section: Introductionmentioning
confidence: 99%